Physical activity and pain - Łosień, Tomasz; Mędrak, Anna; Plaskacz, Paweł; Bajerska, Izabela; Reut, Magdalena; Dragon, Emilia; Polko, Martyna; Cebula, Aleksandra (Journal of Education, Health and Sport, 2017)
Introduction: Undertaking physical activity is often associated with the appearance of proverbial "sourdoughs". DOMS (Delayed Oneset Muscle Soreness), or delayed musculoskeletal muscle pain, known as the aforementioned "soreness", is a consequence of intense physical activity for microtraumas of muscle fibers. In physical medicine, there are many methods to reduce the pain or discomfort of DOMS, including cold baths, gel wraps, hot baths. The literature, however, can be found with reports about the high importance of pain after training in the life of people practicing sports, both professionally and amateur, because its occurrence gives a sense of well-performed training and its effectiveness. The aim of the study: 1) Do the pain after training treat as an integral part of the training?, 2) Are regular athletes striving to develop pain after training?, 3) Do regular sports people often use treatments to prevent "sourdough"?, Material and methods: 149 people participated in the study, including 91 women aged from 13 to 24 years (x = 17.1, SD = 3.7) and 58 men aged 18 to 27 years (x = 21.8; SD = 2 4). They were athletes from UKS Ósemka in Wejherowo and students of the Silesian Medical University in Katowice. An original survey containing 30 closed questions was used. The questions concerned the type of physical activity to be practiced, the pain associated with physical exertion, the time of training, and the prevention of sourdough. The statistical analysis consisted of the performance of descriptive statistics.Results:The analysis showed that the pain after the training, according to the respondents, is an integral part of the training. Regular sports practitioners tend to obtain muscular pain in training. The use of treatments preventing sourdough is not very common among the respondents.